Biogenic Composite Filaments Based on Polylactide and Diatomaceous Earth for 3D Printing - Dobrosielska, Marta (Materials (Basel), 2020)
New composites containing a natural filler made of diatom shells (frustules), permitting the modification of polylactide matrix, were produced by Fused Deposition Modelling (3D printing) and were thoroughly examined. Two mesh fractions of the filler were used, one of <40 µm and the other of 40−63 µm, in order to check the effect of the filler particle size on the composite properties. The composites obtained contained diatom shells in the concentrations from 0% to 5% wt. (0−27.5% vol.) and were subjected to rheological analysis. The composites obtained as filaments of 1.75 mm in diameter were used for 3D printing. The printed samples were characterized as to hydrophilic–hydrophobic, thermal and mechanical properties. The functional parameters of the printed objects, e.g., mechanical characteristics, stability on contact with water and water contact angle, were measured. The results revealed differences in the processing behavior of the samples as well as the effect of secondary granulation of the filler on the parameters of the printing and mechanical properties of the composites.